2023
DOI: 10.1186/s12889-023-15040-z
|View full text |Cite
|
Sign up to set email alerts
|

A situation analysis on postmenopausal women’s self-care needs and priorities in Tehran: a population-based study

Abstract: Background Women need special care during and after menopause. Due to the emphasis of the World Health Organization on promoting self-care in postmenopausal women, this study aims to analyze the situation and prioritize the self-care needs of postmenopausal women in the Tehran-Iran. Methods This was a descriptive-analytical study on 486 postmenopausal women aged 46–85 years living in Tehran in 2021. The Subjects were recruited using a multi-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Likewise, in a study by Shiri-Mohammadabad and Afshani [ 46 ], self-care was low among women living in marginal parts of the city. The need to increase self-care behaviours across different populations of women with and without major health issues is evident from previous research [ 47 , 48 ]. Also, the cultural barriers to practising self-care and breast self-examination have been prevalent in many regions, comparable with the present study [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a study by Shiri-Mohammadabad and Afshani [ 46 ], self-care was low among women living in marginal parts of the city. The need to increase self-care behaviours across different populations of women with and without major health issues is evident from previous research [ 47 , 48 ]. Also, the cultural barriers to practising self-care and breast self-examination have been prevalent in many regions, comparable with the present study [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that self-care for the prevention of the coronavirus among women with or without a medical condition is not significantly different. Although some studies found that people with medical conditions such as cancer, cardiovascular or pulmonary diseases have more self-care and seek more prevention methods [ 39 41 ] the measures as well as the tools for measurement of self-care for the prevention of the coronavirus are different from the prevention of other medical conditions [ 23 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As adherence to PMGs was the focus of this study, the questionnaire was developed based on the recommendations for women's reproductive health and self-care that were posted on reliable organizations' websites, such as Women's Preventive Services Initiatives (WPSI) 2021 recommendations for well-woman care [24], WHO women's health [25], and PMGs recommended by the Ministry of Health of Saudi Arabia [22]. The survey tool included questions related to adherence to PMGs [26].…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…The final score range was between 34 and 190. The following equation was used to convert the total score and the scores for each domain into a standardized score between 0 and 100: (X − Min Score/Max − Min Score) [26].…”
Section: Self-care Questionnairementioning
confidence: 99%